SPAK Deficiency Attenuates Chemotherapy-Induced Intestinal Mucositis - Tien-Yu Huang (Frontiers Media S.A., 2021)
IntroductionSte20-related protein proline/alanine-rich kinase (SPAK) affects cell proliferation, differentiation, and transformation, and sodium and chloride transport in the gut. However, its role in gut injury pathogenesis is unclear.ObjectiveWe determined the role of SPAK in chemotherapy-induced intestinal mucositis using in vivo and in vitro models.MethodsUsing SPAK-knockout (KO) mice, we evaluated the severity of intestinal mucositis induced by 5-fluorouracil (5-FU) by assessing body weight loss, histological changes in the intestinal mucosa, length of villi in the small intestine, pro-inflammatory cytokine levels, proliferative indices, and apoptotic indices. We also evaluated changes in gut permeability and tight junction-associated protein expression. Changes in cell permeability, proliferation, and apoptosis were assessed in SPAK siRNA-transfected 5FU-treated IEC-6 cells.Results5-FU-treated SPAK-KO mice exhibited milder intestinal mucositis, reduced pro-inflammatory cytokine expression, increased villus length, good maintenance of proliferative indices of villus cells, decreased apoptotic index of enterocytes, reduced gut permeability, and restoration of tight junction protein expression (vs. 5-FU-treated wild-type mice). Under in vitro conditions, siRNA-mediated SPAK-knockdown in IEC-6 cells decreased cell permeability and maintained homeostasis following 5-FU treatment.ConclusionSPAK deficiency attenuated chemotherapy-induced intestinal mucositis by modulating gut permeability and tight junction-associated protein expression and maintaining gut homeostasis in murine small intestinal tissues following gut injury. The expression of SPAK may influence the pathogenesis of chemotherapy-induced intestinal mucositis.